2008
DOI: 10.1021/ic801028m
|View full text |Cite
|
Sign up to set email alerts
|

Amidolithium and Amidoaluminum Catalyzed Synthesis of Substituted Guanidines: An Interplay of DFT Modeling and Experiment

Abstract: The synthesis of substituted guanidines is of significant interest for their use as versatile ligands and for the synthesis of bioactive molecules. Lithium amides supported by tetramethylethylenediamine have recently been shown to catalyze the guanylation of amines with carbodiimide. In this report, density functional theory (DFT) calculations are used to provide insight into the mechanism of this transformation. The mechanism identified through our calculations is a carbodiimide insertion into the lithium-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 70 publications
3
33
0
Order By: Relevance
“…In addition to the guanidino function, this ligand offers the pyridine N atom for metal coordination. It was prepared according to a literature procedure [16] (for analytical data, see ref. [17] ) and subsequently brought to reaction with ZnMe 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the guanidino function, this ligand offers the pyridine N atom for metal coordination. It was prepared according to a literature procedure [16] (for analytical data, see ref. [17] ) and subsequently brought to reaction with ZnMe 2 .…”
Section: Resultsmentioning
confidence: 99%
“…L1H 2 was synthesized as described previously. [40,41] IR spectra were recorded with a BIORAD Excalibur FTS 3000 instrument. NMR spectra were recorded with BRUKER Avance II 400 or BRUKER Avance DPX AC200 spectrometers.…”
Section: Methodsmentioning
confidence: 99%
“…The ligands were prepared by the reaction between N,NЈ-diisopropylcarbodiimide and 2-aminopyridine (for L1H 2 ) [40,41] or 2-aminoquinoline (for L2H 2 ) with catalytic AlClMe 2 . In addition to the guanidino N atoms, these ligands bind to the Zn centre through the additional N atom in the aromatic ring.…”
Section: Reactions With Acyclic Guanidinesmentioning
confidence: 99%
“…), further calculations predicted that aluminum amides could also function as active catalysts for the guanylation of amine. [53] The commercially readily available alkyl aluminums, such as AlMe 3 (Scheme 33. ), AlEt 3 , and AlEt 2 Cl, could serve as excellent catalyst precursors for the catalytic addition of amines to carbodiimides, yielding quantitatively their corresponding trisubstituted guanidines.…”
Section: From Substituted Methaniminesmentioning
confidence: 99%
“…), lacking the aryl group which according to them was not responsible for receptor recognition by π-stacking. These rather contained a hydrophobic substituent and a carboxymethyl substitution and were found to be tasteless or to have significantly lower 53 sweetness potency than the corresponding trisubstituted compounds. However, they did not study the effect of nitro and cyano substituted aryl substituents and identified guanidinoacetic acid as the pharmacophore responsible for non sweet taste of the synthesized guanidines.…”
Section: High-potency Sweetenersmentioning
confidence: 99%